2013
DOI: 10.4103/0973-029x.119760
|View full text |Cite
|
Sign up to set email alerts
|

Trends in frequency and duration of tobacco habit in relation to potentially malignant lesion: A 3 years retrospective study

Abstract: Background:Oral cancer is one of the most debilitating and disfiguring of all malignancies; it is one of the most frequently occurring cancers in the body. The high incidence of oral cancer in India has been attributed to widespread tobacco usage among the population either in chewable or smoked form.Aim:In the current study, we retrospectively analyzed 191 cases (2007-2009) of potentially malignant oral lesions, which had been biopsied in our hospital, in order to assess their relationship with tobacco usage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Therefore, the extent of OS in the body can be convincingly administered by evaluation of MDA and GSH, which were found to be reliable markers. Despite the high prevalence of pre-cancerous lesions in India and their potential to undergo malignant transformation (16), very few studies have evaluated serum and salivary MDA and GSH in oral pre-cancer patients. Hence, the present study was carried out to evaluate and compare serum and salivary MDA and GSH in oral leukoplakia and OSCC patients, and to establish the diagnostic efficacy of saliva in evaluating salivary levels of MDA and GSH in oral pre-cancer and OSCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the extent of OS in the body can be convincingly administered by evaluation of MDA and GSH, which were found to be reliable markers. Despite the high prevalence of pre-cancerous lesions in India and their potential to undergo malignant transformation (16), very few studies have evaluated serum and salivary MDA and GSH in oral pre-cancer patients. Hence, the present study was carried out to evaluate and compare serum and salivary MDA and GSH in oral leukoplakia and OSCC patients, and to establish the diagnostic efficacy of saliva in evaluating salivary levels of MDA and GSH in oral pre-cancer and OSCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…4 OSMF a precancerous condition as we know, can progress to OSCC, and approximately 30% of oral cancers in India are attributable to areca nut/gutkha chewing. 5 Epidemiological and in vitro experimental studies have shown that chewing areca nut is the major etiological factor for OSMF.…”
Section: Discussionmentioning
confidence: 99%
“…4 Thus the habit of chewing Gutkha has not only given rise to increased prevalence of OSMF in younger generation but also increased incidence of oral cancer in the same group, shifting the incidence rate of oral cancer from adult age group to younger, which is a global concern.…”
Section: Discussionmentioning
confidence: 99%
“…Current use of two or more types of tobacco products was common, even among students who used tobacco products 1-5 days during the preceding 30 days: 77.3% for cigar smokers, 76.9% for cigarette smokers, 63.4% for smokeless tobacco users, and 54.8% for e-cigarettes users. In one retrospective study conducted by Garget.al (20) in Barananki, Uttar Pradesh, 81.7% consumed tobacco more than five times a day.…”
Section: Tobacco Practices Of Participantsmentioning
confidence: 99%